2021
DOI: 10.1590/1678-4324-2021190276
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Starch Extracted from the Stem of Pineapple Plant (Ananas comosus) - an Agro Waste from Pineapple Farms

Abstract: The present study focused on the use of pineapple plant stem, which is an agro-waste, for the production of starch (11.08 % ± 0.77). Characters were studied using X-ray diffraction, nuclear magnetic resonance spectroscopy (NMR), fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), differential scanning calorimetry (DSC) and rheological methods. The granular size of stem starch was comparatively smaller than corn starch granules. The X-ray diffraction data revealed that stem starc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 42 publications
1
10
0
Order By: Relevance
“…Pineapple stem waste, a byproduct of a proprietary bromelain extraction process, was obtained from Hong Mao Biochemicals Co., Ltd., (Rayong, Thailand). In general, the process involves crushing peeled pineapple stems to disrupt the cell structure and extract liquid by centrifugation [ 28 ]. The remaining solid material was dried under the sun for a few days and further ground into a powder using a grinder.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pineapple stem waste, a byproduct of a proprietary bromelain extraction process, was obtained from Hong Mao Biochemicals Co., Ltd., (Rayong, Thailand). In general, the process involves crushing peeled pineapple stems to disrupt the cell structure and extract liquid by centrifugation [ 28 ]. The remaining solid material was dried under the sun for a few days and further ground into a powder using a grinder.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, our group started investigating pineapple stem starch (PSS) as a promising material for a variety of applications. This is because the PSS has a relatively high amylose content and can be obtained from pineapple field waste, which is abundantly available in Thailand [ 26 , 27 , 28 ]. We reported that the PSS film exhibits good properties, such as high water resistance, low water absorption, and good mechanical strength, while still being readily biodegradable [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thailand is one of the major pineapple producing countries with a total cultivating area of approximately 93 310 hectares (Rinju & Harikumaran-Thampi, 2021). After pineapple fruit harvesting, large amounts of pineapple leaves and stems become agricultural waste.…”
Section: Introductionmentioning
confidence: 99%
“…Hereafter, the starch is denoted as PSS. Only recently has more attention been paid to exploring different ways to utilize this PSS [ 31 , 32 , 33 , 34 , 35 , 36 ]. To the best of our knowledge, there is very limited work on the use of PSS as packaging material.…”
Section: Introductionmentioning
confidence: 99%